Lipoprotein lipase activity in the adipose tissue of rats adapted to controlled feeding schedules - Reichl, D. (1972)
1. The relationships between nutritional state, lipoprotein lipase activity in epididymal fat-pads, and the concentrations of glucose, insulin and unesterified fatty acids in the plasma were studied in rats that had been adapted for 3 weeks to one of two controlled feeding schedules. In one of these, rats had access to food for 14h during each 24h period, and in the other, they had access to food for 14h during each 48h period. Groups of animals were killed at different times during the 14h when they had access to food and during the following period when they were deprived of food. 2. Low lipoprotein lipase activity, low concentrations of plasma glucose and insulin and high concentrations of plasma unesterified fatty acids were found in rats deprived of food for 34h. Feeding resulted in increases in lipoprotein lipase activity and in the concentrations of glucose and insulin in the plasma. Enzyme activity continued to increase during the first 6–9h of the feeding period. 3. After adapted rats had been deprived of food for 12–16h there was a marked and unexpected increase in lipoprotein lipase activity; this occurred even when the rats were kept in an isolated environment. 4. The findings suggest that factors other than the absolute concentrations of insulin and glucose in the blood can exert a considerable influence on lipoprotein lipase activity in the epididymal fat-pad of a rat.